Korruption und globale öffentliche Güter - Eigen, Peter; Eigen-Zucchi, Christian (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2003)
Corruption control is an important input into the production of public goods at the national and at the global level, including sound economic management, well-functioning markets, and reliable human security. Eventually corruption control is itself a public good, because its benefits are largely nonrival and nonexcludable. As the case study of Transparency International shows, civil society has emerged as an effective partner of government and private actors in generating information about the deleterious effects of corruption, raising public awareness, and placing the issue of corruption firmly on domestic and international agendas.